Syphilitic infection: a study on the factors of the innate humoral immune response - N. K. Levchik; N. V. Zilberberg; M. V. Ponomareva; O. A. Belykh (Лечащий Врач)
For the purpose of studying the immunopathogenesis and the search for novel biomarkers for the assessment of syphilitic infection activity, we analyzed B1 cells, that are responsible for basal protection and primary immune reactivity and for generating broad specificity antibodies, and estimated the frequency of occurrence of different autoantibodies. B1 cells are an innate subpopulation of B cells in the fetal hematopoiesis responsible for natural antibody production in the absence of exogenous stimulation. The protective function of B1 cells is to provide protection during the lag phase, the latent period necessary for the deployment of adaptive/acquired immunity mechanisms upon encountering an infectious agent, and in the regulation of subsequent immune responses. B1 cells produce antibodies that bind with low affinity to microbial structures common to various pathogens. Subsequent contact with the antigen leads to an increase in affinity, an increase in antibody titer and the formation of their stable level. Peripheral blood levels of B1(CD19+CD5+) cells were evaluated using flow cytometry in 96 patients with syphilis. Elevated proportions of B1 cells relative to all B lymphocytes have been documented in 44% (95% CI 34-55%) patients. No significant difference was seen regarding clinical form of the disease, gender, age, HIV coinfection, Jarisch – Herxheimer reaction, and antibody titres of non-treponemal tests. There was no statistical correlation between B1 cells and other B- and T-cell subsets. Antibodies against oxidized low-density lipoprotein and cardiolipin were detected more frequently than antibodies against mitochondrial antigen M2, modified citrullinated vimentin, cyclic citrullinated peptide, nuclear antigens, myeloperoxidase, proteinase 3, Fc portion of immunoglobulin G. Overall, the results indicate that B1 cells and phospholipidspecific antibodies are involved in the immune response in syphilis. Improving understanding of the immune response to Treponema pallidum may help develop new diagnostic approaches.